Validations of three-dimensional wake models with the wind field measurements in complex terrain. (15th December 2019) - Sun, Haiying; Gao, Xiaoxia; Yang, Hongxing
Abstract: This paper aims to validate the analytical three-dimensional wake models by the wind data measured at a complex-terrain hilly wind farm in China. The wake models take into account the variation of wind speed in the vertical direction. The profiles of wind speeds were scanned by two moveable lidars. Two scanning modes were adopted to obtain the profiles of wind speed in vertical and horizontal directions, respectively. When validating the wake model for a single wind turbine in the vertical direction, the model can predict the wind speeds with acceptable accuracy, especially at positions beyond 10D downstream distance or above 100 m height. Some large errors were found at positions less than 40 m height. Wind speeds in two symmetrical side sections showed different distributions at the same downwind positions. When validating the wake model for multiple wind turbines in horizontal direction, the model also had a reliable accuracy at the far wake positions and near the inflow measuring site, but it cannot predict the wind deficits before an operating wind turbine and was not accurate in some complex-terrain situations. Suggestions and factors were given to be considered for improving the wake models in the future. Highlights: Original analytical three-dimensional wind turbine wake models are presented. The expression of wake models is simple and its computational cost is low. Wake measurements are conducted in a complex-terrain wind farm. The wake models are validated by the experimental data and turn to have good accuracies. Findings are summarized from the experimental results.